Penerapan Pembelajaran Pendidikan Kesetaraan Paket B Berbasis Kurikulum Merdeka Di SPNF SKB 1 Kota Samarinda - Diah Wulandari; Yudo Dwiyono; Andi Ismail Lukman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to: 1) Describe the implementation of package B equivalency education learning based on the independent curriculum at SPNF SKB 1 Samarinda city, 2) describe the factors that influence the success of the process of implementing package B equivalency education learning based on the independent curriculum at SPNF SKB 1 Samarinda city. This research rhis is descriptive research using a qualitative approach. Data sources for this research include heads of institutions, tutors and students studying at SPNF SKB 1 Samarinda city. Data collection uses observation, interviews and documentation studies. The data analysis technique uses the Mile and Huberman Model which includes data reduction, data presentation and conclusions. Triangulation was carried out to explain the validity of the data using source interviews and techniques. The results of the research show that: 1) The learning process for equivalent education package B based on the independent curriculum in SKB 1 samarinda city consists of three stages, namely planning learning, implementing learning, and assessing learning, 2) Factors that influence the success of implementing curriculum-based equivalent education package B learning. Independence, namely for internal factors, namely physical factors, and external factors, namely family, family economic conditions, and understanding of parents.